Tween80 Coating in Enhancing Physicochemical Stability, Kinetics and Release Mechanism of Layered Double Hydroxide-Ferulate - Sharifah Norain binti Mohd Sharif, Norhayati binti Hashim, Illyas bin Md Isa, Maizatul Najwa Binti Jajuli, Norlaili binti Abu Bakar (Tanjung Malim, 2024)
Tween80 Coating in Enhancing Physicochemical Stability, Kinetics and Release Mechanism of Layered Double Hydroxide-Ferulate by Sharifah Norain binti Mohd Sharif, Norhayati binti Hashim, Illyas bin Md Isa, Maizatul Najwa Binti Jajuli, Norlaili binti Abu Bakar